Strength training & player development: road to the World Cup 2022 - Mendez-Villanueva, A. (Striving for excellence summit. Strength training in football. From performance to prevention and rehabilitation, 2018)
A well-developed capacity of the neuromuscular system to control and drive football movements is highly desirable to successfully compete against better-ranked opponents. The ability of the neuromuscular system to functionally control movements, for instance, enables football players to generate and co-ordinate complex, whole-body movements in order to effectively solve game-related tasks and to avoid joint and muscle damage. Thus, it is believed that football performance can be enhanced and injury risk reduced by appropriate and systematic exercise interventions targeting neuromuscular factors. The long-term methodological framework being implemented by the Qatar National Team leading to the World Cup 2022 is presented.